SPEECH ACTS AND POWER RELATIONS IN THE UNDERGRADUATE EFL LEARNER’S ORAL PRESENTATION - Yonathas Seran Suri; Imanuel Kamlasi (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2026)
Oral presentations require the effective communication of ideas while managing interpersonal dynamics and institutional expectations. This study explored the types of speech acts employed by an EFL learner during an English oral presentation and examined the dynamics of power relations found in the discourse. The research employed a qualitative design using the Interaction Analysis Method (IAM). The data were obtained from a documentary recording of a speech performance, available on the YouTube link for the National English Speech Contest hosted by the English Education of Universitas Timor. The participant focused on the first-place winner as the subject of analysis. The speech was transcribed and analyzed using Austin’s and Searle’s frameworks of speech acts. The findings reveal that the speech includes five types of speech acts: assertive (47%), directive (24%), expressive (13%), commissive (11%), and declarative (5%). The dominant use of assertive and directive speech acts shows that the speaker's primary goal was to inform and persuade the audience. Furthermore, the data identified several power markers, such as epistemic power, deontic power, affective power, moral commitment power, and performative power. These power markers demonstrate how the speaker constructs authority, influences the audience, and negotiates relational dynamics through strategic language choice. The study enhances comprehension of pragmatic competence in the English as a Foreign Language (EFL) context and has pedagogical implications for teaching public speaking and presentation skills.